Cutibacterium acnes biofilm forming clinical isolates modify the formation and structure of Staphylococcus aureus biofilms, increasing their susceptibility to antibiotics. (August 2022) - Abbott, Carmel; Grout, Elena; Morris, Trefor; Brown, Helen L.
Abstract: Cutibacterium acnes (formally Propionibacterium acnes ) is frequently identified within surgical device related infections. It is often co-isolated from infection sites with other opportunistic pathogens. Recent studies have demonstrated that C. acnes is able to form biofilms and when co-cultured with Staphylococcus spp . both inhibitory and stimulatory effects have been reported across several studies. Here, we investigated the biofilm-forming ability of 100 clinical C. acnes isolates from various infection sites in human patients, both deep tissue and superficial, followed by an investigation of how the supernatants of C. acnes cultures influenced the attachment and maturation of Staphylococcus aureus NCTC 6571 biofilms. All of the C. acnes isolates were able to form biofilms in vitro, although biofilm biomass varied between isolates. Nineteen isolates were weakly adherent, 33 were moderately adherent and the majority (48) showed strong adherence. The presence of C. acnes sterile supernatants reduced the biomass of S. aureus cultures, with a > 90% reduction observed in the presence of several of the C. acnes isolates. We observed that this decrease was not due to C. acnes affecting S. aureus viability, nor due to the presence of propionic acid. Biofilm maturation was however delayed over a 24-h period as was biofilm surface structure, although initial (up to 8 h) surface attachment was not affected. We hypothesis that this defective biofilm maturation is the cause of the observed biomass decrease. In turn, these altered biofilms showed a greater susceptibility to antibiotic treatments. In contrast the presence of C. acnes supernatant in planktonic (defined as a free moving, non-surface attached population within the liquid column) S. aureus cultures increased antibiotic tolerance, via a currently undefined mechanism. This study suggests that complex interactions between C. acnes and other opportunistic pathogens are likely to exist during colonisation and infection events. Further investigation of these interactions may lead to increased treatment options and a better prognosis for patients. Highlights: Cutibacterium acnes isolates were able to form biofilm in vitro . Supernatant from C. acnes cultures reduced biofilm biomass of S. aureus biofilms. This affect was not driven by pH or S. aureus growth rate changes. S. aureus surface attachment was unaffected, but biofilm maturation was restricted. C. acnes supernatant altered the susceptibility of S. aureus to antibiotics.